PHB synthase from Streptomyces aureofaciens NRRL 2209 - Ramachander, TVN; Rawal, SK (FEMS Microbiology Letters, 2005)
An similar to4.9 kb Sau3A I genomic DNA fragment from the Streptomyces aureofaciens NRRL 2209 aiding in the biosynthesis of PHB in recombinant Escherichia coli has been sequenced and analysed for phaC gene. The putative phaC(sa) gene of 2 kb is 79.1% GC rich and encodes a 63.5 kDa protein. It expressed under its own promoter and significant PHA synthase activity was detected in the recombinant E coli. This is the first putative PHA synthase gene reported from a Streptomyces sp. with serine as the active nucleophile in the conserved lipase box. The phaC(sa) was found in close proximity to a regulatory gene, which apparently regulated the phaC expression. (C) 2004 Federation of European Microbiological Societies. Published by Elsevier B.V. All rights reserved.
Keywords: PHA synthase; PHB; Streptomyces

Optimization of the production of a maltooligosaccharides producing amylase from the alkalophilic streptomyces lonarensis strain NCL 716 using SVR modeling - Sharma, Trupti K.; Bhadane, Vaibhav A.; Kumar, Lalitha S.; Rele, Meenakshi V.; Bhawar, Gajanan; Rahman, Imran (Starch-Starke, 2013)
The Streptomyces lonarensis strain NCL 716 hydrolyses starch to produce a mixture of maltotriose (G3) and maltotetraose (G4) along with maltose (G2). The objective of the present work was to determine an optimum cost effective media composition for the production of a-amylase from this strain. The most influential factor was found to be starch while the least influential factor found was peptone by PlackettBurman method. Peptone amount was kept constant throughout the fermentation. Peptone, which is one of the expensive media components was used at a concentration of 1?g/L, which made the optimum media composition cost effective. A support vector regression-based process model was developed for approximating the non-linear relationship between the fermentation operating variables and the a-amylase yield. Multicanonical Jump Walk Annealing, a stochastic optimization technique is used to obtain optimal operating variables to maximize amylase yield. The maximum amylase activity thus obtained was in good agreement with the experimental values at the optimized levels. The optimum media composition obtained by this method was: yeast extract: 4.53?g/L, starch: 20.246?g/L, K2HPO4: 0.0827%, MgSO4: 0.15%, peptone: 1?g/L. A maximum enzyme activity of 297?U/mL, which was achieved using the above approaches compares well with the activity of reported amylases producing maltooligosaccharides.
Keywords: Alkaline a-amylase; Optimization; Streptomyces; Support vector regression analysis

Anti-fungal potentials of extracellular metabolites of western ghats isolated streptomyces sp NII 1006 against moulds and yeasts - Jayamurthy, Himani; Sajna, Kuttavan Valappil; Dastager, Syed Gulam; Pandey, Ashok (Indian Journal of Experimental Biology, 2014)
Realization of hazardious effects of chemical fungicides has led to an interest in the usage of biocontrol agents. The present study, therefore, evaluates the biocontrol efficacy of Western Ghats (India) soil bacterial isolates. A potential strain NII 1006 was evaluated for its antagonistic property against a diverse range of moulds and yeasts. The strain was characterized morphologically, biochemically and molecularly, which revealed the isolate belonged to Streptomyces genus. Organic solvent extracts of NII 1006 culture filtrates inhibited the growth of the test pathogens indicating that growth suppression was due to extracellular anti-fungal metabolites present in the culture filtrates. The strain produced extracellular chitinase enzyme in addition to some stable partially purified anti-fungal compounds. Morphological changes such as hyphae degradation into debris and abnormal shapes were observed in test fungi and yeast grown on potato dextrose broth that contained the NII 1006 culture filtrate. The cell free supernatant has a tolerance to wide range of pH, temperature and enzymes such as lipase and protease. The biocontrol potential of NII 1006 strain may be correlated significantly with their ability to produce antibiotics as well as extracellular hydrolytic enzymes particularly chitinolytic enzyme.
Keywords: Anti-fungal activity; Biocontrol; Extracellular anti-fungal metabolites; Streptomyces

Development of bioconjugate from streptomyces tyrosinase and gold nanoparticles for rapid detection of phenol constituents - Zainab, Mazhari Bi Bi; Madhusudhan, D. N.; Raghavendra, H.; Dastager, Syed Gulam; Dayanand, Agsar (Indian Journal of Experimental Biology, 2014)
Most of the phenol compounds are toxic and have been considered as hazardous pollutants. Several physicochemical and biological methods are available to detect and monitor the phenol pollutants in water and soil. In the present study, phenol constituents of winery, paper and plastic industrial effluents were successfully detected employing tyrosinase-gold nanoparticles bioconjugate. The synthesis of extracellular tyrosinase and gold nanoparticles was achieved by a single isolate of Streptomyces sp. DBZ-39. Enhanced production (369.41 IU) of tyrosinase was produced in submerged bioprocess employing response surface method with central composite design. Extracellular gold nanoparticles synthesized (12-18 nm) by Streptomyces sp. DBZ-39 were characterized with TEM, EDAX and FTIR analysis. A rapid detection (within 10 min) of phenol constituents from winery effluents was achieved by bioconjugate, when compared to tyrosinases and gold nanoparticles independently. Streptomyces tyrosinase could exhibit relatively a better performance than commercially available mushroom tyrosinase in the detection of phenol constituents. Winery effluent has shown much higher content (0.98 O.D) of phenol constituents than paper and plastic effluents based on the intensity of color and U.V absorption spectra.
Keywords: Bioconjugate; gold nanoparticles; Phenol detection; Streptomyces; Tyrosinase